Tunable, gain switched Ti3+:Al2O3 laser pumped by intracavity frequency doubled, Nd3+:YLF laser - Gorajek, Łukasz; Gałecki, Łukasz (Photonics Letters of Poland, 2009)
A room-temperature, coherently pumped, tunable titanium-sapphire laser was constructed and examined. For excitation diode pumped, a neodymium laser with intracavity frequency doubling was deployed. The Nd:YLF laser was emitting 1.3 mJ-pulses with the pulse duration of 50 ns. After conversion in LBO crystal, the 1.2 mJ of output energy was obtained at the 523 nm of the output wavelength. A tunable titanium-sapphire laser has been running in the gain switching regime. The 0.12 mJ output energy was obtained in a FWHM pulse length of 40 ns for the best case, which corresponded to 3 kW peak power. Tunability range was found between 753 nm and 820 nm. The pulse repetition rate was set to 200 Hz. Full Text: PDF References: H. S. Karlsson, G. Chiaia, U. O. Karlsson,"A system for time- and angle-resolved photoelectron spectroscopy based on an amplified femtosecond titanium:sapphire laser system", Review of Scientific Instruments , vol.67, no.10, pp.3610-3615, Oct 1996 URL: http://ieeexplore.ieee.org/stamp/stamp.jsp?arnumber=4993509&isnumber=4993468[CrossRef] S. Hannemann, E. J. van Duijn, W. Ubachs,"A narrow-band injection-seeded pulsed titanium:sapphire oscillator-amplifier system with on-line chirp analysis for high-resolution spectroscopy", Review of Scientific Instruments , vol.78, no.10, pp.103102-103102-9, Oct 2007 URL: http://ieeexplore.ieee.org/stamp/stamp.jsp?arnumber=5003147&isnumber=5003143[CrossRef] 10.1063/1.2789690 V. Nagarajan, E. Johnson, P. Schellenberg,"A compact versatile femtosecond spectrometer", Review of Scientific Instruments , vol.73, no.12, pp.4145-4149, Dec 2002[CrossRef] R. Cubeddu, A. Pifferi, P. Taroni, et al.,"Noninvasive absorption and scattering spectroscopy of bulk diffusive media: An application to the optical characterization of human breast", Applied Physics Letters , vol.74, no.6, pp.874-876, Feb 1999 URL: http://ieeexplore.ieee.org/stamp/stamp.jsp?arnumber=4901378&isnumber=4901342[CrossRef] T.A. King, A. Charlton,"Near infrared solid state lasers for medical applications", Optical Techniques and Biomedical Applications, IEEE Colloquium on , vol., no., pp.7/1-7/6, 14 Jun 1991 URL: http://ieeexplore.ieee.org/stamp/stamp.jsp?arnumber=181794&isnumber=4621 E. J. Salumbides, S. Hannemann, E. J. van Duijn,"A narrowband Ti:Sapphire-based pulsed laser system for precise frequency metrology in the deep UV", Lasers and ElectroOptics, 2007 and the International Quantum Electronics Conference. CLEOE-IQEC 2007. European Conference on , vol., no., pp.1-1, 17-22 June 2007 URL: http://ieeexplore.ieee.org/stamp/stamp.jsp?arnumber=4386812&isnumber=4385799 J. C. J. Koelemeij, W. Hogervorst, W. Vassen,"High-power frequency-stabilized laser for laser cooling of metastable helium at 389 nm", Review of Scientific Instruments , vol.76, no.3, pp.033104-033104-4, Mar 2005 URL: http://ieeexplore.ieee.org/stamp/stamp.jsp?arnumber=5001477&isnumber=5001472[CrossRef] V. Bardinal, R. Legros, C. Fontaine,"In situ measurement of AlAs and GaAs refractive index dispersion at epitaxial growth temperature", Applied Physics Letters , vol.67, no.2, pp.244-246, Jul 1995 URL: http://ieeexplore.ieee.org/stamp/stamp.jsp?arnumber=4886784&isnumber=4886750[CrossRef] 10.1063/1.114681 M. Yumoto, Y. Maeda, M. Yamashita, et al.,"Rapidly and Random Wavelength Tuned Mid-Infrared Laser", Lasers and ElectroOptics, 2007 and the International Quantum Electronics Conference. CLEOE-IQEC 2007. European Conference on , vol., no., pp.1-1, 17-22 June 2007 URL: http://ieeexplore.ieee.org/stamp/stamp.jsp?arnumber=4385830&isnumber=4385799 E. Sali, E. Ignesti, S. Cavalieri et al.,"A tuneable, single-mode titanium-doped-sapphire laser source with variable pulse duration in the nanosecond regime", Optics Communications 282 (2009) 3330?333[CrossRef]